Aysce
Well-Known Member
- Joined
- Jun 24, 2011
- Messages
- 2,393
- Gender
- Male
- HSC
- 2012
The polynomial
has a zero at x = 1. Find k hence, factorise P(X).
Originally I found K as -9 as I subbed in x=1 and let P(1) = 0, but when I factorised it, it didn't come with the right answer so yeahh.. Anyways answer is
P(X) = (x-1)(x-7)(x+2)
Nothing like maths on a friday night.. :L
Originally I found K as -9 as I subbed in x=1 and let P(1) = 0, but when I factorised it, it didn't come with the right answer so yeahh.. Anyways answer is
P(X) = (x-1)(x-7)(x+2)
Nothing like maths on a friday night.. :L